Data from: Within-season synchrony of a masting conifer enhances seed escape - Archibald, Devan W.; McAdam, Andrew G.; Boutin, Stan; Fletcher, Quinn E.; Humphries, Murray M. (Dryad, 2011)
Predator satiation resulting from interannual reproductive synchrony has
been widely documented in masting plants, but how reproductive synchrony
within a year influences seed escape is poorly understood. We evaluated
whether the intra-annual reproductive synchrony of individual white spruce
trees (Picea glauca) increased seed escape from their primary predispersal
seed predator, North American red squirrels (Tamiasciurus hudsonicus).
Trees with cones that matured synchronously relative to those of other
trees within red squirrel territories were significantly more likely to
escape squirrel predation in years with both low and superabundant levels
of cone production, generating a significantly positive linear selection
differential for increasing intra-annual reproductive synchrony. Thus,
this masting plant escapes seed predation in numbers through interannual
synchrony in seed production and in time through intra-annual synchrony of
seed availability.
TreeINFO
Keywords: Ecology: evolutionary; Interactions: plant/herbivore; Canada; Picea glauca; Yukon; Reproduction: strategies; Interactions: plant/animal; Interactions: predation; Selection: natural; Tamiasciurus hudsonicus